2016
DOI: 10.1108/rsr-02-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Learning commons reference collections in ARL libraries

Abstract: Purpose-This paper explores the changing role of the reference collection in learning commons at ARL member libraries. Design/Methodology/Approach-A 15 question survey was sent to managers at academic research libraries with membership in the Association of Research Libraries (ARL). Respondents were asked about their learning commons and reference collections. To increase the sample size, the researchers conducted phone interviews using the same questions with a random sample of individuals from the same targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…With the rapid growth of electronic resources available through the Internet, scholars and students can search for relevant information remotely on their mobile devices. This trend has transformed the library into a new venue with fewer printed materials circulations but more requests on the social and educational patterns of learning, teaching, and research support (Pierard and Bordeianu, 2016;Wang et al, 2016). Many university libraries worldwide consider ways of improving library learning spaces to cater to actual user needs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid growth of electronic resources available through the Internet, scholars and students can search for relevant information remotely on their mobile devices. This trend has transformed the library into a new venue with fewer printed materials circulations but more requests on the social and educational patterns of learning, teaching, and research support (Pierard and Bordeianu, 2016;Wang et al, 2016). Many university libraries worldwide consider ways of improving library learning spaces to cater to actual user needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Makerspaces are also established in some libraries or learning commons to allow users to create objects with new technologies such as 3D printing (Cao et al , 2020). While librarians are planning to implement learning commons in their libraries, different aspects of the space planning, such as the size of printed collection, integration with new technologies and proportion of quiet study and collaborative space are needed to consider to satisfy the changing demands of patrons (Blummer and Kenton, 2017; DeFrain and Hong, 2020; Huang and Wang, 2021; Pierard and Bordeianu, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As elaborated by Pierard and Bordeianu "the concept of the information commons and more recently the learning commons has emerged and evolved in the library literature for nearly two decades". 19 Donald Beagle suggested that "the information commons is a service environment organized in support of learning whereas a learning commons is the product of collaboration that aligns the resources of that environment with broader learning initiatives or outcomes as determined "through a cooperative process" by multiple campus groups and units". 2,19 As comprehended by Schmidt & Kaufman "The focus of a learning commons goes beyond helping students "manage" information to helping them "manage" their learning.…”
Section: Literature Review -Learning Commonsmentioning
confidence: 99%
“…19 Donald Beagle suggested that "the information commons is a service environment organized in support of learning whereas a learning commons is the product of collaboration that aligns the resources of that environment with broader learning initiatives or outcomes as determined "through a cooperative process" by multiple campus groups and units". 2,19 As comprehended by Schmidt & Kaufman "The focus of a learning commons goes beyond helping students "manage" information to helping them "manage" their learning. Rather than highlighting access to computers, software, and multi-media support, a learning common emphasizes a range of programs and services to help students in their learning tasks.…”
Section: Literature Review -Learning Commonsmentioning
confidence: 99%